Comparative Evaluation of Effective Exercise Intensity Using Metabolic Equivalent and Anaerobic Threshold - Ugras, Seda; Ozcelik, Oguz (Wiley, 2019)
[Abstract Not Available]
Keywords: Anaerobic threshold; metabolic equivalent; oxygen uptake